1992
DOI: 10.1007/bf02050541
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoid tumors of Meckel's diverticula

Abstract: Two cases of carcinoid tumors in Meckel's diverticula are reported. Additionally, data of 104 published cases of carcinoids in this rare location are analyzed. The average age of the patients is 56.6 years and corresponds to the age of patients with ileal carcinoids. Carcinoids in Meckel's diverticula also resemble ileal carcinoids in their biological behavior more than they do appendiceal carcinoids. Tumors larger than 5 mm have a marked risk to metastasize. By the time symptoms are present, 77 percent of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Individuals most likely to develop complications are those aged 40 years or younger, those with diverticula two centimeters in length or greater, and those containing heterotopic tissue[5]. When complications do present, gastrointestinal bleeding is the most common clinical symptom, generally related to an ulcer caused by secretion from associated gastric mucosa[6]. …”
Section: Introductionmentioning
confidence: 99%
“…Individuals most likely to develop complications are those aged 40 years or younger, those with diverticula two centimeters in length or greater, and those containing heterotopic tissue[5]. When complications do present, gastrointestinal bleeding is the most common clinical symptom, generally related to an ulcer caused by secretion from associated gastric mucosa[6]. …”
Section: Introductionmentioning
confidence: 99%
“…27 In 1992, Neis et al summarized 104 published cases of Meckel diverticulum cancer (MDC). 13 In their review of 13,715 carcinoids from the Surveillance, Epidemiology, and End Results (SEER) database, Modlin et al observed that 0.48% to 0.74% of all carcinoids in the body occurred in the MD. 28 To the best of our knowledge, there have been no single population-based analysis of the epidemiological and prognostic features of primary MD malignancies.…”
mentioning
confidence: 99%
“…Similar to the cystadenoma, histological diagnosis was unknown, but carcinoid tumours are the most common malignant tumours of Meckel's diverticulum with two thirds of patients remaining asymptomatic at initial diagnosis [2]. Tumour size influences the likelihood of metastases as does the gender, but with early metastases even in small tumours, aggressive surgical management is justified [1,2,7,9].…”
Section: Discussionmentioning
confidence: 99%
“…Carcinoid tumours are rare, and the presence of a carcinoid tumour in Meckel's diverticulum is so rare, that to date, less than 120 cases have been described in the literature [1,2]. Carcinoid tumours are neuroendocrine tumours originating from the neural crest and can be diagnosed at any age [3].…”
Section: Introductionmentioning
confidence: 98%